A low-temperature internal heating strategy without lifetime reduction for large-size automotive lithium-ion battery pack. (15th November 2018) - Jiang, Jiuchun; Ruan, Haijun; Sun, Bingxiang; Wang, Leyi; Gao, Wenzhong; Zhang, Weige
Graphical abstract: Highlights: A low temperature internal heating strategy with AC+DC for lithium-ion battery pack. The permissible AC and DC are determined to circumvent lithium-ion deposition. A simple soft-switching circuit with low loss is designed for heating battery pack. The essentially uniform temperature distribution within battery pack during heating. No lifetime reduction of battery pack after 600 repeated heating experiments. Abstract: To overcome the long-standing challenge of poor performance of large-size automotive lithium-ion battery pack at low temperature, an internal self-heating strategy without lifetime reduction is proposed. A new method superimposing the discharge current on alternating current for self-heating is developed to prevent lithium-ion deposition, which not only avoids the measurement difficulty of potential and impedance of anode electrode, but also circumvents inconsistency problem of battery pack. The permissible alternating current and direct current are determined to avoid lithium-ion deposition. An effective yet simple soft-switching circuit is designed for heating of large-size automotive lithium-ion battery pack. The battery pack is warmed up from −20.8 °C to 2.1 °C within 600 s, where the temperature difference among twelve batteries is below 1.6 °C, implying the essentially uniform temperature distribution. Based on the performance analysis for battery pack, no obvious loss of lithium inventory is found and no lifetime reduction is observed after 600 repeated heating tests due to the suitable over-potential of anode electrode and no substantial thermal-induced aging stress. The proposed self-heating strategy, validated for heating uniformly and effectively without lifetime reduction, is of high potential to deliver a practical solution to poor performance of large-size automotive lithium-ion battery pack in cold conditions.